2015
DOI: 10.1155/2015/412327
|View full text |Cite
|
Sign up to set email alerts
|

mir-21 Overexpressing Mesenchymal Stem Cells Accelerate Fracture Healing in a Rat Closed Femur Fracture Model

Abstract: MicroRNAs are small noncoding RNAs involved in numerous biological processes. Emerging pieces of evidence suggest that microRNAs play important roles in osteogenesis and skeletal homeostasis. Recent studies indicated the significant regulation function of mir-21 in osteogenesis in vitro, but little information is known about its veritable functions in vivo. In the present study, we aimed to investigate the effect of mir-21 intervention on osteogenic differentiation of rats bone marrow derived mesenchymal stem … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
76
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 69 publications
(78 citation statements)
references
References 42 publications
2
76
0
Order By: Relevance
“…In addition, icariin can also induce osteoclast apoptosis and inhibit differentiation of osteoclasts and bone resorption (Zhang et al, ). MicroRNAs (miRNAs), a class of small non‐coding RNAs of approximately 22 nucleotides that post‐transcriptionally regulate target mRNAs, have been reported to promote osteoblast differentiation, including miR‐21 (Meng et al, ; Sun et al, ; Wei et al, ; Li et al, ). Accumulating evidence has revealed the stimulatory effect of miR‐21 on osteoblastic differentiation (Meng et al, ; Sun et al, ; Wei et al, ; Li et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, icariin can also induce osteoclast apoptosis and inhibit differentiation of osteoclasts and bone resorption (Zhang et al, ). MicroRNAs (miRNAs), a class of small non‐coding RNAs of approximately 22 nucleotides that post‐transcriptionally regulate target mRNAs, have been reported to promote osteoblast differentiation, including miR‐21 (Meng et al, ; Sun et al, ; Wei et al, ; Li et al, ). Accumulating evidence has revealed the stimulatory effect of miR‐21 on osteoblastic differentiation (Meng et al, ; Sun et al, ; Wei et al, ; Li et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Using systemic downregulation of miR‐92a (via antimir‐92a) in a mouse femoral fracture model, the authors found increased callus volume and neovascularization that resulted in enhanced fracture repair (Figure ) . Sun et al engineered miR‐21 overexpressing bone marrow–derived mesenchymal stem cells (BMSCs) and injected these cells into the fracture site of rat transverse femoral fractures. At 7 days postfracture, they observed accelerated endochondral ossification, greater bone volume, and ultimately a biomechanically stronger bone.…”
Section: Mirnas and Fracture Repairmentioning
confidence: 99%
“…At 7 days postfracture, they observed accelerated endochondral ossification, greater bone volume, and ultimately a biomechanically stronger bone. Given their data, the authors suggested that this may be a potential therapeutic approach to enhance fracture repair …”
Section: Mirnas and Fracture Repairmentioning
confidence: 99%
“…Then, osteoblasts and chondrocytes calcify and develop into immature bone. Ultimately, bone remodeling is activated together with osteoclasts . In light of this knowledge, exogenous intervention of BMSCs in fracture healing has been reported to be feasible.…”
Section: Introductionmentioning
confidence: 99%